Cellular neural networks and visual computing : foundation and applications - Chua, Leon O., 1936- (Cambridge University Press, 2002)
This is a unique undergraduate level textbook on Cellular Nonlinear/neural Networks (CNN) technology. The many examples and excercises, including a simulator accessible via the Internet, make this book an ideal introduction to CNNs and analogic cellular computing for students, researchers and engineers from a wide range of backgrounds.